Strategi Pengembangan Usaha Kelepon Wahyu Di Kecamatan Gempol Kabupaten Pasuruan - Oktaviani, Dewi Anggun; Lidyana, Novita; Damayanti, Ratika Pradisya (Agrotechbiz : Jurnal Ilmiah Pertanian, 2022)
The purpose of this study was to find out the right strategy to develop the Kelepon Wahyu business in Gempol Pasuruan. The research subject is the owner of the Kelepon Wahyu business in Gempol, Pasuruan. This study uses a qualitative approach and uses SWOT analysis as the data analysis method. The results of this study indicate the most appropriate strategy that can be applied to develop Kelepon Wahyu's business further by improving its manufacturing and production process infrastructure and human resources.Keywords: Kelepon Wahyu, Strengths, Weaknesses, Opportunities and Threats.